2018
DOI: 10.1080/17461391.2018.1551424
|View full text |Cite
|
Sign up to set email alerts
|

Parental sport achievement and the development of athlete expertise

Abstract: This study sought to examine how parental sport involvement and attainment were related to the eventual level of competitive sport attained by their children. Athletes (n = 229) were divided into three skill level groups (elite: n = 139; pre-elite: n = 33; non-elite: n = 57), based on the peak competition level achieved in their career, which were compared using chi-squares tests of independence and analyses of variance according to parents sport characteristics provided through the Developmental History of At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…In this study, the sports practice presented itself as a potent element in the process of socialization, of establishing new affective bonds, capable of promoting feelings of belonging and pleasure provided by the sports activity itself, as corroborated by the literature 1,5,13,14 . Studies highlight that emotional and affective support, focusing on play and enjoyment and interest in the child's sport have an important role in guaranteeing their healthy psychological development 1,14,15 .…”
Section: Skating and Competing: The First Influencessupporting
confidence: 63%
See 3 more Smart Citations
“…In this study, the sports practice presented itself as a potent element in the process of socialization, of establishing new affective bonds, capable of promoting feelings of belonging and pleasure provided by the sports activity itself, as corroborated by the literature 1,5,13,14 . Studies highlight that emotional and affective support, focusing on play and enjoyment and interest in the child's sport have an important role in guaranteeing their healthy psychological development 1,14,15 .…”
Section: Skating and Competing: The First Influencessupporting
confidence: 63%
“…A similar result was found in a study with former athletes of rhythmic gymnastics and their parents, which revealed the tendency of mothers to provide daily and constant support through praising, direct care, frequent contact with the coaches, and making costumes for competitions, while fathers' assistance happened through financial and material support 21 . The effects of parental gender in relation to children's sport participation were also observed by Wilson et al 13 who found that the competitive sport history of fathers, but not of mothers, was associated with athletes' skill level. Such findings reinforce the importance of amplifying the understanding of the parental role in the development of their children's sport participation.…”
Section: Family Models and Maternal Participationsupporting
confidence: 63%
See 2 more Smart Citations
“…For instance, the need for an extensive period of deliberate practice (Ericsson et al, 1993) is now established as a basic requirement for the development of expertise, but the concept of deliberate practice is relatively new to the science of human skill acquisition and expertise. Similarly, the current focus on psychological qualities such as grit (Duckworth et al, 2007) and self-regulation (McCardle et al, 2019), perceptual cognitive issues such as the quiet eye (Vickers, 2016) and representative learning designs (Pinder et al, 2011), and environmental factors such as quality of the early developmental environment (Baker et al, 2009) and the role of athletic parents (Wilson et al, 2019) each reflect relatively new developments in this field of research.…”
mentioning
confidence: 99%